Innovation and Digitalization: Driving Forces for Corporate Competitiveness and Longevity - Amri, Amri; Isnanto, Burham; Saputro, Seno Hadi; Bakti, Ferry (Universitas Bina Sarana Informatika, 2025)
In the face of rapid technological advancements and market shifts, companies must adapt and enhance their competitiveness to ensure long-term survival. This study explores the impact of innovation, digital transformation, productivity, and employment on organizational competitiveness and their influence on corporate longevity and sustainability in the Bangka Belitung Islands, Indonesia. Employing survey methods and analyzing data using double regression, simple regression, smartPls, and SPSS, the study surveyed 120 respondents from various industrial sectors. The results reveal that innovation, productivity, and jobs significantly and positively impact companies' competitiveness, while digital transformation has a lesser effect. Additionally, the study found that a company's competitiveness positively and significantly influences its existence and survival. The research significantly contributes to understanding the factors affecting competitiveness and long-term viability in the digital economy, highlighting the crucial role of innovation, productivity, and job quality in enhancing competitive advantage. The findings provide a basis for strategic decision-making at the company level and the development of public policies that foster business growth and resilience within the Belitung Framework